Engajamento no trabalho docente: refinamento de modelos teóricos e de mensuração para contextos educacionais. - Tagava, Regina Fujiko (2021)
This thesis starts from the substantial challenges presented to the management and evaluation of education, whose implications may improve the organizational conditions that optimize the well-being and health of teachers. We proposed six studies. The first study identified the structuring categories for the management of teaching work through a literature review in four thematic categories: practices and teacher training, working conditions, policies and regulation of work, and worker's health. The contributions propose a research perspective that aims to optimize the educational practices in Brazil and Latin America. The second study aimed to review the literature on definitions and theoretical models of engagement, identifying that the level of theorization of perspectives varied between personal and organizational characteristics, contextualized in the work environment, making it possible to categorize the definitions of the construct in perspectives: contrary to Burnout, affective, multidimensional, organizational and three-dimensional motivational. The study's contribution was to scale the concepts of work engagement better to improve understanding of the phenomenon, optimizing the future theoretical application. The third study reviewed the assessed measures and factors of work engagement in the literature, identifying the theoretical basis, the predominant factors, the sample characteristics, the nationality of the investigation and the psychometric evidence. The contribution was to qualify that among the different measures, the UWES - Utrecht Work Engagement Scale has optimized psychometric properties in different contexts, which indicates the theoretical and empirical robustness of the elaborations based on multidimensional models of work engagement. The fourth study intended to review the literature's variables related to work engagement, identifying participants from different areas of activity in this review and highlighting various variables with positive, negative and inconclusive effects on work engagement. The contribution relies on clarifying the construct's predictors and consequences to optimize the political and practical propositions for developing work engagement. The fifth study aimed to seek confirmatory validity evidence for the internal structure of the Teacher Engagement at Work Scale (EEP) in the Brazilian context, recognizing the confirmation of appropriate psychometric evidence for the EEP. The contribution lies in the conceptual, theoretical improvement in social engagement with peers and cognitive-behavioural engagement to optimize the assessment proposal. The sixth study sought evidence of validity for the internal structure of the Reduced Scale of Engagement in the Work of Teachers (R-EEP) in the Brazilian context, identifying that the validity indicators demonstrated adequate internal structure, internal consistency and criterion validity. The contribution lies in redesigning the theoretical and empirical evaluation model proposed for R-EEP. Finally, the conclusions of this thesis are presented, which integrate the contributions made to the educational field and work to act in front of educational management and promotion of better working conditions for teachers, with engagement in work as a central variable. The main implication of the current thesis is the possibility to employ theoretical and empirical models for educational management.